THU0079 Dendritic cell (dc) subsets in rheumatoid arthritis (ra) analysed by 4 colour flow cytometry. (1st June 2001) - O'Donnell, JL; Summers, KL; Rothwell, A
Abstract : Background: Distinct myeloid (MDC) and lymphoid (LDC) DC subsets have been described in humans which are thought to regulate the nature and magnitude of the immune response. 1 MDC have been associated with a T helper 1(TH1) mediated response while LDC have been associated with a TH2 mediated response. 2 Inappropriate regulation of DC function may result in diseases such as RA. Objectives: The composition, co-stimulator molecule expression (CD80, CD86, CD40, 41BB-L) and activation (CD83, CD69) state of these two DC subsets was compared between autologous peripheral blood (PB), synovial fluid (SF) and synovial tissue (ST) from patients with RA undergoing joint replacement surgery. DC were defined as lineage negative (CD3-, CD14-, CD16-, CD19- and CD20-) HLA-DR positive cells. MDC were defined as CD11c+ and LDC as CD11c- cells. Methods: Whole blood lysis was used to isolate peripheral blood white cells and size exclusion used to distinguish peripheral blood mononuclear cells (PBMC). Centrifugation was used to isolate cells from freshly drawn SF. ST cells were isolated by mechanical extraction of coarsely minced tissue. Fluorochrome labelled monoclonal antibodies and flow cytometry were used to identify and quantitate cell populations and cell surface proteins of interest. All procedures were carried out either on ice or with cells at 4ºC. Results: In the 5 RA patients peripheral blood DC constituted 0.47% (mean, range 0.11–1.28) of PBMC. The ratio of MDC to LDC was 1:3.8. Both MDC and LDC expressed weak/low levels of activation and co-stimulator molecules. DC constituted 2.06% (mean, range 0.78–3.76) of SF mononuclear cells with a ratio of MDC to LDC of 9:1. MDC but not LDC expressed moderate levels of both activation and co-stimulator molecules. ST DCs constituted 8.41% (mean, range 0.7–22.7) with MDCs making up 100% of DCs in the 5 samples analysed. These MDC expressed high levels of both activation and co-stimulator molecules. In normal healthy adults (n = 50) DC constituted 1.07% (mean, median 0.96, 95% confidence limits 0.43–2.5) of PBMC with a MDC to LDC ratio of 1:1. 3 Conclusion: These preliminary results suggest that MDC play an important role in the pathogenesis of joint disease in RA and support the view that RA is predominantly a TH1 mediated disease. References: Banchereau J, et al . Immunobiology of dendritic cells. Annu Rev Immunol. 2000;18:767–811 Rissoan MC, et al . Reciprocal control of T helper cell and dendritic cell differentiation. Science 1999;283:1183–6 McKenzie J, et al . Personal communication, 2000